EVALUASI PROGRAM RUMAH SUSUN SEDERHANA SEWA (RUSUNAWA) YOS SUDARSO KOTA PEKANBARU - Nur Azliana; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The rapid population growth will add to the complexity of the development problems being faced, especially those related to settlements. Due to limited land, people with low incomes are unable to obtain adequate land and housing, and therefore illegal settlements have emerged. In order to overcome this, the city government of Pekanbaru issued a policy in the form of a Simple Rental Flats (Rusunawa) program that can solve the problem of illegal housing that often occurs in cities and can help Low-Income Communities (MBR) in meeting the needs of a place to live that is decent and healthy. The purpose of this research is to find out how to evaluate Yos Sudarso Pekanbaru City Rental Flats program and to find out the inhibiting factors in achieving Yos Sudarso Pekanbaru City Rental Flats Program. This study used a qualitative method with a case study approach, in which the determination of the informants used purposive sampling technique and the required data, both primary and secondary data, were obtained through observation, interviews and documentation and then analyzed based on the research problem. The results showed that: Yos Sudarso's Simple Rental Flats (Rusunawa) in Pekanbaru City has not been not run optimally. It can be seen from the input evaluation that there are still shortcomings such as the lack of facilities provided by the manager. There are still obstacles in the evaluation process, the are residents who are not target, the are still many Rusunawa residents who are in arrears to pay rent. Inhibiting factors in this study were limited costs and occupants’ level of awareness. Keywords: Program, Evaluation